SOLITARY PULMONARY NODULE A RARE CASE: Solitary Pulmonary Nodule - Majeed, Farhan Ahmed; Jamal, Shahid; Hanif, Muhammad Shoaib; Din, Najam -ud-; Wyne, Adeel (Pakistan Armed Forces Medical Journal, 2015)
A middle aged man presented with a solitary pulmonary nodule. He had a diagnostic dilemma as the CT guided FNAC was inconclusive. The frozen section exam reported it to be malignant so a lobectomy was performed for this lesion. The final histopathology report confirmed it to be a very rare tumor of extra skeletal synovial sarcoma.